Trustworthy Behavior in Students - Lailatul Izzah; Yuliza, Eva (Nathiqiyyah, 2023)
Interesting psychological research is interpersonal relationships, one of the factors that influences the success and failure of interpersonal relationships is trust. Amanah includes all religious duties or responsibilities addressed to humans which include matters in this world and the hereafter. Trust has two components, namely positive personality aspects and the ability to complete tasks. This research uses descriptive qualitative methods with semi-structured interview techniques. Apart from that, this research used observation techniques with two participants. The aim of this research is to find out how students who live in boarding houses behave confidently. The research results show that trustworthy people carry out tasks in a trustworthy, responsible and honest manner.